2021
DOI: 10.1038/s41541-021-00298-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of persistent modulation of intestinal microbiota on SIV/HIV vaccination in rhesus macaques

Abstract: An effective vaccine to prevent HIV transmission has not yet been achieved. Modulation of the microbiome via probiotic therapy has been suggested to result in enhanced mucosal immunity. Here, we evaluated whether probiotic therapy could improve the immunogenicity and protective efficacy of SIV/HIV vaccination. Rhesus macaques were co-immunized with an SIV/HIV DNA vaccine via particle-mediated epidermal delivery and an HIV protein vaccine administered intramuscularly with Adjuplex™ adjuvant, while receiving dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“… 22 A more recent study also supported a link between the gut microbiome and gut CCR5 expression by showing that probiotic intake reduced CCR5 expression on CD4 + T cells in the gut of macaques. 23 These studies together support that MSM-microbiome mediated increases in CD4 + CCR5 + T cells in the rectum has potential implications for increased risk of HIV transmission and that the gut microbiome may be a viable target for disease prevention. More work will be needed, however, to validate that the gut microbiome of MSM actually induces increased transmission of HIV in vivo and the particular microbes and mechanisms involved.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“… 22 A more recent study also supported a link between the gut microbiome and gut CCR5 expression by showing that probiotic intake reduced CCR5 expression on CD4 + T cells in the gut of macaques. 23 These studies together support that MSM-microbiome mediated increases in CD4 + CCR5 + T cells in the rectum has potential implications for increased risk of HIV transmission and that the gut microbiome may be a viable target for disease prevention. More work will be needed, however, to validate that the gut microbiome of MSM actually induces increased transmission of HIV in vivo and the particular microbes and mechanisms involved.…”
Section: Discussionmentioning
confidence: 65%
“…The concept that an altered microbiome can influence rectal HIV transmission via induction of CCR5 expression on CD4 + T cells is supported by two recent studies in macaques. 22 , 23 Specifically, rhesus macaques from two different sources had significantly different rates of infection against repeated low-dose SHIV intrarectal challenge, and this was associated with an altered gut microbiome and an increase in activated CD4 + CCR5 + Ki67 + T cells in the rectal mucosa of the susceptible group. 22 A more recent study also supported a link between the gut microbiome and gut CCR5 expression by showing that probiotic intake reduced CCR5 expression on CD4 + T cells in the gut of macaques.…”
Section: Discussionmentioning
confidence: 99%
“…After probiotic administration, the authors observed significant increases in colonic and lymph node myeloid cells, IgA + B-cells, increased LN TFH cells and intestinal innate lymphocyte type 3 s, and decreased activation of colonic CD4 + T-cells. Similarly, Klatt et al observed that co-administration of probiotic Visbiome with adjuvanted SIV Gag and HIV Env DNA/HIV gp140 trimer protein vaccination strategy, decreased target cell frequency, increased SIV gag-specific CD4 + and CD8 + T-cell responses, and increased IgA + LN B-cells [ 114 ].…”
Section: Microbiome Therapies: Too Little or Too Much?mentioning
confidence: 99%
“…Though widely reported to have beneficial effects on gastrointestinal immunity, oral probiotic therapy in macaques has not been shown to extensively remodel the intestinal microbiome [ 47 , 114 ] perhaps suggesting the potential for a finite number of taxa to influence susceptibility to SIV or HIV. In an effort to create a gastrointestinal pathogen-free ( Campylobacter spp.…”
Section: Microbiome Therapies: Too Little or Too Much?mentioning
confidence: 99%
See 1 more Smart Citation